Uses of Internet and Mobile Technology in Health Systems for the Elderly: A Case Study of Hong Kong - Lam, Sanches; Chung, Winnie (International Journal of Interactive Mobile Technologies (iJIM), 2010)
To investigate the impact of training the elderly to use the Internet and mobile computer devices in order to become more active in their health care. This study utilized semi-structured interviews and surveys. Five themes emerged from the interviews that described participants' motivations and barriers they experienced when using the mobile devices and Internet. Survey data revealed that levels of computer anxiety decreased and levels of efficacy increasing after training. Conclusion: Training the elderly to use the Internet lowered levels of computer anxiety. In addition, participants used the information retrieved from the Internet to become more active in their own health care.